Challenges in Automation, Robotics and Measurement Techniques Proceedings of AUTOMATION-2016, March 2-4, 2016, Warsaw, Poland - Szewczyk, Roman; Zieliński, Cezary; Kaliczyńska, Małgorzata (Advances in Intelligent Systems and Computing, 2016)
This book presents the set of papers accepted for presentation at the International Conference Automation, held in Warsaw, 2-4 March of 2016. It presents the research results presented by top experts in the fields of industrial automation, control, robotics and measurement techniques. Each chapter presents a thorough analysis of a specific technical problem which is usually followed by numerical analysis, simulation, and description of results of implementation of the solution of a real world problem. The presented theoretical results, practical solutions and guidelines will be valuable for both researchers working in the area of engineering sciences and for practitioners solving industrial problems. .